Impact of the use of the WS-01 bottle nipple in feeding therapy for preterm infants - Jara Cabrera, Gerson; Bernal Vallejos, Eduardo; Figueroa Quezada, Barbara; Hernández Osses, Martín; Arend Peña , Marina (Revista de Investigación en Logopedia, 2026)
The preterm neonate presents with immature oral reflexes and ineffective coordination of sucking, swallowing, and breathing. These alterations can lead to serious complications such as penetration and aspiration. The role of the speech-language pathologist is to ensure a safe feeding route and a transition toward full oral feeding. The purpose of this study was to determine the impact of using the preterm nipple (WS-1 code 01319) in habilitation and/or rehabilitation therapy for feeding in preterm infants. A longitudinal, descriptive, and comparative study was conducted. Using simple random sampling, a sample of 90 preterm infants was obtained. The intervention consisted of stimulation of the orofacial musculature, non-nutritive sucking exercises, and the use of Pigeon WS-01 preterm nipples. The control group was composed of 23 preterm infants who underwent the same exercises but used a traditional nipple. The study was approved by the ethics committee of the Araucanía Sur Health Service. Among the findings, in the group of preterm newborns who used the WS-01 nipple, 81% were discharged with the removal of the nasogastric tube (NGT) and oral feeding within the first 12 days, compared to only 9% in the control group that did not use the nipple. The use of the nipple has proven to be an effective tool that reduces hospitalization days and shortens the transition time from NGT to exclusive oral feeding, which can be complemented with breastfeeding.
Keywords: Preterm newborn; sucking; swallowing; bottle feeding; oral feeding; bottle nipple